Pengaruh Kualitas Pelayanan dan Atribut Produk terhadap Kepuasan Konsumen : Survei pada Konsumen Shopee di Kota Tasikmalaya - Via Octaviani, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the simultaneous and partial effect of Service Quality and Product Attributes on Consumer Satisfaction (Survey of Shopee consumers in Tasikmalaya City). The research method used in this study is a quantitative research method with a survey approach. The sampling technique used is incidental sampling and the sample taken is 100 respondents. The analytical tool used is multiple regression equation. The results showed that Service Quality and Product Attributes simultaneously had a significant effect on Shopee consumer satisfaction in the City of Tasikmalaya. Service quality partially has a significant effect on Shopee consumer satisfaction in Tasikmalaya City. Product attributes partially have a significant effect on Shopee consumer satisfaction in Tasikmalaya City.